The use of Artificial Intelligence in CSR Reporting from the Perspective of SMEs - Taattola, Olivia (My University, 2024)
Corporate social responsibility reporting has become a strategic asset for today’s businesses. Much of the existing literature on CSR reporting focuses on the perspective of large corporations and lacks focus on small and medium sized enterprises (SMEs). SMEs make up 99,8% of corporations in the EU and research on the perspective of SMEs in CSR reporting practises is therefore relevant to the adaptation of responsible business. The rapidly evolving field of artificial intelligence (AI) offers possibilities for its utilization in the different phases of CSR reporting. AI has the potential to serve as a CSR reporting tool for SMEs. This thesis aims to explore how artificial intelligence can be used as a tool in CSR reporting from the perspective of SMEs. The topic is explored through three sub questions, which attempt to shed light on the importance of CSR reporting, the implications of CSR reporting on SMEs, and the challenges associated with SMEs’ CSR reporting. Using appropriate theoretical frameworks, and a thorough look into existing literature, this thesis finds that adequate CSR reporting is important in order to respond to stakeholder demands and adapt to evolving reporting regulation. CSR reporting by SMEs positively influences corporate reputation, enhances communication with stakeholders, increases customer loyalty, and contributes to corporate performance. SMEs face challenges in compiling, assuring and using CSR reports due to knowledge gaps, limited resources, technological obstacles, organizational barriers, lack of support and overwhelming policies and regulations. Artificial intelligence can be utilized by SMEs as a CSR reporting tool in data management, production of reports, enhancing of accuracy and credibility, use of the report for decision-making, as well as in increasing stakeholder engagement. This thesis contributes to existing research on the application of artificial intelligence for business operations, such as CSR reporting, and attempts to resolve the challenges faced by SMEs when it comes to this type of reporting. The managerial implications of these findings include adaptation of artificial intelligence tools in CSR reporting to provide more effective, efficient and accurate CSR communication.

Yritysvastuuraportoinnista on tullut nykypäivän yrityksille strateginen voimavara. Suuri osa yritysvastuuraportointia käsittelevästä kirjallisuudesta keskittyy suurten yritysten näkökulmaan, pienten ja keskisuurten yritysten (pk-yritysten) näkökulman sijaan. Pk-yritykset muodostavat 99,8 % EU:n yrityksistä, minkä takia tutkimus pk-yritysten yritysvastuuraportointiin liittyvistä teemoista on merkittävää vastuullisen liiketoiminnan edistämisen kannalta. Tekoälyn nopea kehitys mahdollistaa sen hyödyntämisen yritysvastuuraportoinnin eri vaiheissa. Tekoälyllä on potentiaalia toimia pk-yritysten yritysvastuuraportoinnin työkaluna. Tämän tutkielman tavoitteena on tarkastella, miten tekoälyä voidaan hyödyntää strategisena työkaluna pk- yritysten yritysvastuuraportoinnissa. Tutkielma vastaa tavoitteeseen kolmen alakysymyksen kautta, joilla pyritään avaamaan yritysraportoinnin tärkeyttä, siihen liittyviä haasteita sekä raportoinnin vaikutuksia pk- yrityksiin. Käyttämällä asianmukaisia teoreettisia viitekehyksiä, ja perehtymällä perusteellisesti olemassa olevaan kirjallisuuteen, tutkielmassa todetaan, että asianmukainen yritysvastuuraportointi on tärkeää: se auttaa vastaamaan sidosryhmien vaatimuksiin ja mukautumaan kehittyvään raportointisääntelyyn. Pk-yritysten toteuttama yritysvastuuraportointi vaikuttaa myönteisesti yrityksen maineeseen, parantaa viestintää sidosryhmien kanssa, vahvistaa asiakassuhteita ja edistää yrityksen suorituskykyä. Pk-yritykset kohtaavat haasteita yritysvastuuraportoinnin laatimisessa, varmistamisessa ja käyttämisessä. Pk-yritysten raportointiin liittyvät haasteet ovat seurausta tietämyksen puutteesta, resurssien rajallisuudesta, teknisistä esteistä, organisaatiollisista rajoitteista, tuen puutteesta sekä monimutkaisista regulaatioista. Pk-yritykset voivat hyödyntää tekoälyä yritysvastuuraportoinnin työkaluna tiedonhallinnassa, raporttien tuottamisessa, tarkkuuden ja uskottavuuden parantamisessa, raporttien hyödyntämisessä päätöksenteossa sekä sidosryhmien sitouttamisessa. Tämä tutkielma täydentää olemassa olevaa tutkimusta tekoälyn soveltamisesta liiketoiminnassa, kuten yritysvastuuraportoinnissa, ja pyrkii ratkaisemaan haasteita, joita pk-yritykset kohtaavat tämän tyyppisessä raportoinnissa. Tutkielman löydöksien hallinnolliset ja käytännön vaikutukset liittyvät tekoälytyökalujen hyödyntämiseen yritysvastuuraportoinnissa, jotta yritysten yritysvastuusta tiedottaminen olisi tehokkaampaa, tuloksellisempaa ja tarkempaa.
Keywords: corporate social responsibility, corporate social responsibility reporting, small and medium sized enterprises, artificial intelligence, yritysvastuu, yritysvastuuraportointi, pienet ja keskisuuret yritykset, tekoäly